ISLAMIC LAW PARADIGM OF EFFORT TO CHILDREN EDUCATIONAL PROTECTION - Lubis, Andi Hakim; Muazzul, Muazzul; Mhd Hasbi, Mhd Hasbi (Proceeding International Seminar of Islamic Studies, 2023)
Central Bureau of Statistics data about the number of children out of school by level of education for the last 3 years showed that there are many children who do not go to school in Indonesia is still apprehensive. The number of children who are not in school From 2019 to 2021 for Elementary and the equivalent  is (0.85), (0.62), (0.65). Whereas Junior High School and the equivalent  in the same year are (6.92), (7.29), (6.77) and Senior High School and the equivalent  in the same year are (23.75), (22.32), ( 21,47). Meanwhile, Islamic teachings place great emphasis on protecting children because children are the next generation of the nation who can disseminate Islamic teachings based on the Quran and Hadith. This study used a qualitative approach which described and analyzed how Islamic law views child protection, especially regarding the fulfillment of children's educational rights. It resulted that the implementation of children's right to education are an important pillar for efforts to increase the degree of humanity and the advancement of human civilization which in Islam is known as hifz al-'aql (maintenance of reason). Islam teaches that education for every human being is very important. Everyone is required to study science until the end of his life. Allah SWT said in the Al-Mujadilah verse 11 which means "Allah will raise up to suitable ranks and degrees those of you who believe and who have been granted knowledge".